2016
DOI: 10.1159/000448991
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Lesions: Prevalence and Clinical Phenotype in Asymptomatic Individuals Aged <b>≥</b>50 Years

Abstract: Background: To assess the prevalence of early confluent/confluent white matter lesions (ec/cWMLs) in asymptomatic individuals aged ≥50 years and to identify associated clinical phenotypes. Methods: Cross-sectional analysis of 141 asymptomatic individuals aged ≥50 years assessed at an outpatient department in France. Brain magnetic resonance imaging was rated using the Fazekas scale. Age-adjusted odds ratios (ORs) and 95% confidence intervals were estimated using logistic models to investigate factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…investigated the presence of white matter lesions in 141 asymptomatic individuals with an average age of 63 years; the prevalence of white matter lesions was found to be 26.2 per cent. The authors concluded that white matter lesions are common in healthy individuals aged over 50 years 14 …”
Section: Discussionmentioning
confidence: 99%
“…investigated the presence of white matter lesions in 141 asymptomatic individuals with an average age of 63 years; the prevalence of white matter lesions was found to be 26.2 per cent. The authors concluded that white matter lesions are common in healthy individuals aged over 50 years 14 …”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup analysis of the SUCCEED survey, we found that 34% of asymptomatic individuals (free of dementia or cognitive complaints) aged ≥50 had understated cognitive impairment, as assessed by poor performance in the Clock-Drawing Test (CDT). 4 The CDT has become one of the most commonly used cognitive screening instruments. The test involves a diverse range of high-level cognitive abilities, such as executive control, visuospatial and visuoconstructive functions, semantic memory, and language skills.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the prevalence of DSWMH lesions was 48.4%. This value was relatively high compared to previous studies, which reported that the prevalence of white matter hyperintensities was 25.9% in 1249 young clinical outpatients [31] and 26.2% in 141 asymptomatic individuals aged ≥ 50 years [32]. In addition, the prevalence of PPD = 4-5 mm and PPD ≥ 6 mm was 59.2% and 16.4%, respectively ( Table 2).…”
Section: Discussionmentioning
confidence: 53%